Sound As A Dramatic Enhancer Through Dialogue And Atmospheric Sound In The Film Budi Pekerti - Sabryan Faza Nasher Abdullah; Rian Prasetya Yunanto (Journal of Interdisciplinary Social Sciences and Humanities, 2026)
Budi Pekerti (2023) explores social issues through the story of a teacher’s struggle against cyberbullying. This study aims to examine how diegetic sound design contributes to the film’s dramatic strength, particularly in the contexts of conflict, suspense, curiosity, and surprise. Using a descriptive qualitative approach, the research analyzes eleven key scenes selected based on their dramatic content and the presence of diegetic sound elements. Data were collected through film observation and literature review to reinforce the theoretical framework. The findings show that on-screen sound such as dialogue and environmental ambience effectively builds tension, conflict, and character development. Meanwhile, off-screen sound adds emotional layers and expands the narrative space, especially in generating moments of surprise. These results affirm that diegetic sound is not merely a complement to visual elements but serves as a significant narrative device that shapes atmosphere and deepens story meaning. This research is expected to serve as a reference for filmmakers and scholars in exploring sound design as an integral component of cinematic storytelling